Character Education Values Reflected in King Tirian's Characterization in C.S. Lewis's The Last Battle - Ni Kadek Riska Aristyawati; Ni Komang Arie Suwastini; I Nyoman Pasek Hadi Saputra (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study aimed to analyze how King Tirian, the protagonist in The Last Battle by C.S. Lewis, reflects the five core character values proposed in the Penguatan Pendidikan Karakter (PPK) framework by Hendarman et al. (2017). Employing a qualitative content analysis design, the study analyzed King Tirian's characterization through the interactive data analysis model of Miles et al. (2014), which consisted of data collection, data condensation, data display, and conclusion drawing. The data were obtained from King Tirian's actions, dialogues, thoughts, and interactions throughout the novel and then categorized according to the five core character values and their sub-values. The findings revealed that all five core character values were reflected in King Tirian's characterization. The religiosity was reflected through his unwavering faith in Aslan, devotion to others, and reverence for Aslan. Nationalism was reflected through his love for Narnia, commitment to protecting its people and sacred land, and willingness to sacrifice for the common good. Mutual cooperation was demonstrated through his collaborative relationships, trust in his companions, and shared responsibility in overcoming challenges in Narnia. Independence was characterized by his strategic decision-making, courage, resilience, and creative problem-solving when facing challenge. Moreover, integrity was reflected through his respect for the dignity of others, commitment to truth and justice, and consistency in upholding moral principles despite personal risks. These findings suggest that The Last Battle story provides meaningful reflections of character values through King Tirian's characterization, which indicate its potential contribution as literary material for supporting character education in educational contexts.